Information Technology and AKI: Alerts, Alarms, Bells and Whistles - Wilson, F. Perry (Adv Chronic Kidney Dis, 2017)
The goal of this review is to describe the rationale for alerting systems for acute kidney injury (AKI), the challenges associated with alert implementation, and the efficacy (or lack thereof) of AKI alerts to date.